A Homologue of the Tryptophan-Rich Sensory Protein TspO and FixL Regulate a Novel Nutrient Deprivation-Induced Sinorhizobium meliloti Locus - Davey, Mary Ellen (American Society for Microbiology (ASM), 2000)
A nutrient deprivation-induced locus in Sinorhizobium meliloti strain 1021 was identified by use of a Tn5-luxAB reporter gene transposon. The tagged locus is comprised of two open reading frames (ORFs) designated ndiA and ndiB for nutrient deprivation-induced genes A and B. Comparison of the deduced amino acid sequences of both ndiA and ndiB to the protein databases failed to reveal similarity to any known genes. The expression of the ndi locus was found to be induced by carbon and nitrogen deprivation, osmotic stress, and oxygen limitation and during entry into stationary phase. To identify regulatory components involved in the control of ndi gene expression, a second round of mutagenesis was performed on the primary ndiB::Tn5-luxAB-tagged strain (C22) with transposon Tn1721. A double-mutant strain was obtained that lacked ndi locus transcriptional activity under all of the inducing conditions tested. The Tn1721-tagged gene showed a high degree of similarity to tryptophan-rich sensory protein TspO from Rhodobacter sphaeroides, as well as to mitochondrial benzodiazepine receptor pK18 from mammals. Induction of the ndi::Tn5-luxAB reporter gene fusion was restored under all inducing conditions by introducing the tspO coding region, from either S. meliloti or R. sphaeroides, in trans. Furthermore, it was found that, in addition to tspO, fixL, which encodes the sensor protein of an oxygen-sensing two-component system, is required for full expression of the ndi locus, but only under low oxygen tension.